Tindak Tutur Direktif pada Lagu Daerah Bolaang Mongondow Bertema ‘Nasihat Orang Tua’ - Andiani Rezkita Nabu (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
As one of the cultural products, the Bolaang Mongondow regional song was created based on social interaction between the Bolaang Mongondow tribal community and its cultural environment. So it is not surprised that regional song lyrics has its own uniqueness compared to other types of discourse. The purpose of this study is to investigate the types and meanings of directive utterances that exist in the discourse of the regional song lyrics of Bolaang Mongondow with the theme